Evolution and Current Trends in Liquid and Supercritical Fluid Chromatography - Fekete, Szabolcs; Grand-Guillaume Perrenoud, Alexandre; Guillarme, Davy (Current Chromatography, 2014)
The current trend in high performance liquid chromatography (HPLC) tends toward the achievement of higher separation efficiency and shorter analysis time. Indeed, better performance in LC has become increasingly important in recent years mainly driven by the challenges of either analyzing more complex samples or increasing the numbers of samples per time unit. In the recent development of particle technology, the use of fully porous sub-2 µm particles and sub-3 µm shell particles have received considerable attention. Beside packed columns, the new generation of silica-based monolithic columns also offers very high separation power. However, to take full advantage of these innovative phases, the chromatographic system has also to be drastically optimized in terms of upper pressure limit and system volume. This revolution in column technology now spreads and covers several modes of liquid chromatography such as reversedphase liquid chromatography (RPLC), hydrophilic interaction liquid chromatography (HILIC), or even supercritical fluid chromatography (SFC). The HILIC and SFC, which can be considered as alternative modes of chromatography, could also be useful to extend the applicability of chromatography towards the analysis of very hydrophilic and lipophilic compounds, respectively. The present review gives an insight about the theory behind the success of current column technology and presents a summary of latest applications, using various modes of one-dimensional chromatography (RPLC, HILIC, SFC). This paper also shows that theoretically expected column efficiency could sometimes be compromised in practical work especially in the case of narrow bore columns.
Keywords: monolith